Analysis of pregnant women with the diagnosis of gestational diabetes mellitus without oral glucose tolerance test confirmation in early pregnancy: Analiza nosečnic z diagnozo nosečnostna sladkorna bolezen, ki ni bila potrjena z oralnim glukoznim tolerančnim testom v zgodnji nosečnosti - Zavratnik, Andrej; Krajnc, Mitja (Acta Medico-Biotechnica, 2021)
Purpose: The aim of this analysis was to determine the proportion of pregnant women referred by gynaecologists to the outpatient diabetes clinic of the University Medical Centre Maribor with a diagnosis of gestational diabetes mellitus (GDM) based on inappropriately measured fasting plasma glucose (FPG). Additionally, we wanted to compare pregnancy outcomes in subgroups diagnosed later as having GDM vs. no–GDM with oral glucose tolerance testing (OGTT) in the 24th to 28th week of pregnancy, but declared as “probably not having GDM” in early pregnancy. Methods: We reviewed retrospectively data on 81 pregnancies referred to our centre, from August 2013 to July 2014, with a diagnosis of early GDM that we did not con-firm with OGTT retesting. After retesting, women were followed up routinely by a gynaecologist, but those with a diagnostic OGTT, performed in the 24th to 28th week, were referred back to a diabetologist. Results: The age of the entire cohort was 30.5±4.7 years, and 91% were ≥25 years old; 40% were overweight before pregnancy. The period of fasting before FPG measurement was less than 8 hours in 36%. When comparing the GDM vs. no–GDM subgroups, a higher proportion of women with GDM were fasted for less than 8 hours before FPG measurement (75% vs. 32%; p=0.022), and birth weight was higher for women with GDM (3778±588 g vs. 3316±618 g; p=0.048). There were no differences in macrosomia, eclampsia, Caesarean delivery and birth trauma. Conclusion: The accuracy of the diagnosis of early pregnancy GDM can be improved by following the FPG measurement protocol. When a single FPG in early pregnancy is near normal we suggest retesting with an OGTT. This approach probably has no adverse effect on pregnancy outcomes.